As medidas coercitivas atípicas em vista do devedor solvente - Vieira, Leandro Rocha (My University, 2026)
This research discusses the atypicality of executive measures in civil procedural law, questioning whether indirect measures can induce a solvent debtor to pay, especially when the debtor acts deliberately to frustrate the execution process. Civil Enforcement is widely regarded as one of the bottlenecks of the Brazilian judicial system. For decades, discussions have revolved around how to provide greater efficiency and effectiveness to it, ensuring that the enforcement of rights is swift, adequate, and effective. One of the actions taken has been expanding the judge's powers to employ all measures capable of ensuring enforcement, even when not explicitly provided for by law. However, there is significant doctrinal, jurisprudential, and academic divergence regarding the broad power granted to judges and, above all, the legitimacy of its application. In this context, the study is justified as it addresses a controversial issue, with atypicality potentially serving as an important tool for enforcement. In conclusion, it was found that atypical or indirect coercive measures adhere to constitutional principles and postulates; that there is a solid basis of parameters and criteria to support the magistrate's choice of atypical measures, through a reasoned decision and the broad exercise of the adversarial process by the parties; that such measures are subsidiary in nature, meaning they can be adopted when typical enforcement methods have been exhausted; that the judiciary possesses mechanisms to control atypicality and correct potential abuses; and, finally, that these measures can serve as an important mechanism of coercion against solvent or habitual (professional) debtors, compelling them to comply with payment obligations. [resumo fornecido pelo autor]
Esta pesquisa discute a atipicidade dos meios executivos no direito processual civilista, ao questionar se medidas indiretas podem induzir o devedor solvente ao pagamento, em especial, quando o executado age deliberadamente com o intuito de frustrar à execução. A Execução Civil é considerada, por muitos, como um dos gargalos do sistema judiciário brasileiro. Há décadas discute-se formas de lhe prover maior eficiência e eficácia, para que a tutela satisfativa seja célere, adequada e efetiva. Uma dessas ações foi a ampliação dos poderes do juiz, para empregar todas as medidas capazes de assegurar a tutela executiva, mesmo quando não previstas em lei. Todavia, há grande divergência doutrinária, jurisprudencial e acadêmica quanto ao amplo poder conferido ao julgador e, sobretudo, quanto à legitimidade de sua aplicação. Nesse contexto, o estudo se justifica por se tratar de matéria controvertida, podendo a atipicidade constituir-se em importante instrumento para a execução. Em conclusão, verificou-se que as medidas coercitivas atípicas ou indiretas observam princípios e postulados constitucionais; que existe uma sólida base de parâmetros e critérios a subsidiar a escolha da medida atípica pelo magistrado, mediante decisão fundamentada e amplo exercício do contraditório pelas partes; que possuem caráter de subsidiariedade, isto é, podem ser adotadas quando esgotados os meios típicos de execução; que o judiciário possui mecanismos para realizar o controle da atipicidade, de forma a corrigir eventuais abusos; e, por fim, que podem ser um importante mecanismo de coerção frente ao devedor solvente ou costumaz (devedor profissional), compelindo-o ao pagamento. [resumo fornecido pelo autor]
Keywords: Processo civil; Execução (Processo civil); Devedores e credores